Development of E-Learning ICT Guidance at Hidayatul Musthafawiyah Salafiyah Islamic Boarding School - Padli, Alvin Faiz Nuthgi; Abdullah, Rijal; Huda, Asrul; Maksum, Hasan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to develop website-based E-Learning on ICT guidance activities at Hidayatul Musthafawiyah Salafiyah Islamic Boarding School. This study uses Research and Development (RandD) methods. This research method uses a 4-D development model to analyze the key stages; defining, designing, developing, and disseminating. The trial was conducted on three learning media experts and 37 students at PPS Hidayatul Musthafawiyah. Descriptive analysis data used in this research activity will include analyzing the validity, practicality, and effectiveness of ICT guidance extracurricular E-Learning. The result shows that the ICT-Counseling extracurricular e-learning verification test score is 96.2%, a valid category. The overall rating of the Practical Aptitude Test is 92.77%, which is an efficient category. The overall effectiveness test rating was 98.51%, indicating that this category was used effectively. This research is in developing a valid, practical, and effective platform in an Islamic boarding school setting. In future research, the effectiveness of the developed e-learning platform can be evaluated through a comparative study with traditional classroom learning or other e-learning platforms. Additionally, further research can be conducted to develop e-learning platforms for other extracurricular activities in Islamic boarding schools.